Epidemiological, Clinical, and Immunological Features of Ghanaian People-Living-with-HIV (Human Immunodeficiency Virus) and Molecular Proof of Cystoisospora belli in Their Stool Samples - Hagen Frickmann; Fred Stephen Sarfo; Betty Roberta Norman; Martin Kofi Agyei; Albert Dompreh; Shadrack Osei Asibey; Richard Boateng; Edmund Osei Kuffour; Martin Blohm; Veronica Di Cristanziano; Torsten Feldt; Kirsten Alexandra Eberhardt (Pathogens)
Cystoisospora belli is a coccidian parasite commonly associated with enteric infections in immunocompromised individuals. The study was conducted to assess epidemiological, clinical, and immunological features of Ghanaian people living with HIV (human immunodeficiency virus) with and without antiretroviral therapy and molecular proof of C. belli-specific nucleic acid sequences in their stool samples. While C. belli was detected in 4.2% (n = 25) of the assessed HIV-positive patients, this was the case for only 1 (1.2%) Ghanaian control individuum without known HIV infection. Associations of cystoisosporiasis in Ghanaian HIV patients with reduced CD4+ T-lymphocyte counts and increased HIV viral loads, immune-activation as indicated by reduced CD4+/CD8+ T-lymphocyte ratios as well as higher expression of HLA-DR+ CD38+ on CD4+ T-lymphocytes, a symptom complex comprising diarrhea, weight loss and a reduced BMI, a trend towards not being on antiretroviral medication, and lacking access to food safety procedures like storing food in refrigerators were shown. The odds ratios (95% confidence intervals) of the associations were 4.47 (1.52–12.09) for the abundance of C. belli DNA and clinical diarrhea, 3.51 (1.42–9.12) for the abundance of C. belli DNA and CD4+ T-lymphocyte counts <200 cells/µL, and 3.66 (1.52–9.01) for the abundance of C. belli DNA and not having a refrigerator in the household. In conclusion, the assessment contributed to existing insight into the epidemiology of cystoisosporiasis in immunosuppressed individuals in resource-limited tropical high-endemicity areas. Chronic diarrhea among people living with HIV should prompt a diagnostic assessment for confirmation or exclusion of C. belli infections in such settings.